The influence of anaerobic muscle activity, maturation and season on the flesh quality of farmed turbot - Roth, Bjørn; Imsland, Albert K.; Stien, Lars Helge; Schelvis-Smit, Rian; Gunnarsson, Snorri; Foss, Atle (Aquaculture International, 2010)
In order to test seasonal, rearing, maturing and anaerobic muscle activity effect on the flesh quality of turbot (Scophthalmus maximus) a total of 80 farmed turbot from three different strains from reared under natural or continuous light were killed by a percussive blow to the head in November (winter, Icelandic strain), March (spring, Portuguese strain) and June (summer, domesticated strain (France turbot)). To test the effect of anaerobic muscle activity, 10 fish were on each occasion pre rigor filleted, where one fillet was used as a control, while the other fillet was electrically stimulated using a squared 5 Hz, 10 V pulsed DC for 3 min. All pre rigor fillets were measured for pH, weighed, wrapped in aluminum foil and stored in polystyrene boxes with ice. After 7 days of storage the fillets were measured instrumentally for pH, drip loss, colour (CIE L* a* b*) and texture properties such as hardness and shear force, while fillet shrinkage and colour (RBG) were evaluated with computer imaging on photographs from a standard lightbox. Results showed that softness of the flesh was mainly influenced by factors associated with growth, such as season, photoperiod and maturation. Anaerobic muscle activity simulated with electrical stimulation caused an increase in drip loss (\1%) and loss of shear force publishedVersion